Beauveria bassiana ribotoxin inhibits insect immunity responses to facilitate infection via host translational blockage. (May 2020) - Yuan, Yi; Huang, Wuren; Chen, Keping; Ling, Erjun
Abstract: Entomopathogenic fungi are promising bio-pesticides. To facilitate infection, fungi recruit multiple virulence factors and deploy different molecular strategies to evade host immunity. Fungal ribotoxins are extracellular secreted ribonucleases (RNases) with ribotoxic cytotoxicity and insecticidal activity. However, it remains unclear whether they have further biological functions. Here we show that the entomopathogenic fungus Beauveria bassiana ribotoxin ( Rib ) contributes to fungal virulence by inhibiting insect host immunity. Gene deletion of Rib (Δ Rib ) resulted in attenuated fungal virulence during infection. Pathogenesis analysis demonstrated that Rib mainly inhibits insect immunity through modulating the reactive oxygen species (ROS) response, suppressing antimicrobial peptides (AMPs) production and retarding hyphae penetration from insect cuticles. To further confirm this immunosuppressive function, recombinant ribotoxin (rRib) protein was purified and co-injected with living or heat-killed bacteria, bacteria-derived peptidoglycan (PGN) and lipopolysaccharide (LPS) separately, which also significantly inhibited the AMPs production in Drosophila fat bodies. Furthermore, co-injection of rRib with Escherichia coli or Staphylococcus aureus significantly enhanced bacterial pathogenicity and facilitated infection. In addition, rRib injection resulted in a global inhibition of protein expression in different tissues of Drosophila adults. This work identified B. bassiana ribotoxin as a key virulence factor that inhibits insect immunity. Highlights: B. bassiana ribotoxin ( Rib ) is an extracellularly secreted virulence factor. Rib inhibits insect immunity responses to facilitate fungal infection. Rib induces ribosomopathies and host translational blockage. Rib inhibits Drosophila host immunity to microbial infection.